Improvement of the Off-State Breakdown Voltage With Fluorine Ion Implantation in AlGaN/GaN HEMTs - Wang, Maojun; Chen, Kevin J. (IEEE TRANSACTIONS ON ELECTRON DEVICES, 2011)
Improvement of the AlGaN/GaN high-electron mobility transistor's (HEMT's) OFF-state breakdown voltage is achieved by implanting (19)F(+) ions at an energy of 50 keV and dose of 1 x 10(12) cm(-2) under the gate region using BF(3) as the source. The charge state of the implanted fluorine ions changes from positive to negative in the AlGaN/GaN structure because of fluorine's strong electronegativity. The negative-charged fluorine ions at the back side of the two-dimensional electron gas can raise the energy barrier of the GaN buffer layer under the channel, effectively blocking the current injected from the source to the high-field region of the GaN channel when the HEMT is biased at OFF-state. The source-injected electrons, if not blocked, could flow to the high-field region and initiate a premature three-terminal OFF-state breakdown in a conventional AlGaN/GaN HEMT. A 38% improvement of the three-terminal OFF-state breakdown voltage and 40% improvement of the power figure-of-merit V(BD-off)(2)/R(on) are achieved in the enhanced back barrier HEMT.